Homes on Borders in Chicano Literature - Tucan Gabriela (Romanian Journal of English Studies, 2019)
In “Borderlands/La Frontera” (1987), Gloria Anzaldúa writes about the “tradition of long walks” (11) across physical and imaginary borders, which defines her Mexican-American people. The borderland is both a space of transit and a state of transition from where the Chicanos venture into unknown territories. Their identity is constructed around and across space(s). In this paper, I seek to examine the Chicanos’ fluid spatial identity in their searches for a real home, in Pat Mora’s “House of Houses”, Sandra Cisneros’ “The House on Mango Street”, Gloria Anzaldúa’s “Borderlands/La Frontera”. I argue that in these literary and autobiographical works, the cosy domestic home is impossible to find because of constant displacement and imposed mobility.